Synthesis of Fatty Alcohol-Based Phosphate Esters - Lee, Ching Shya (2008)
Fatty chemicals based on edible and inedible tallow and a variety of vegetable oils have wide use in plastics industry. At present, there are some limitation and economic competition between plastics additives based on fats and oils and those from fossil fuels (crude oil and natural gas). The large growth of palm oil production in Malaysia and the rapid expansion of oleochemical production facilities in Malaysia imply strong growth for these chemicals in plastics application in the recent years. Oleochemicals has been reported being large used as emulsifiers and stabilizer in polymerization, as auxiliarities for processing and as structural materials in plastics industry. A preliminary study carried out has shown the compatibility between inorganic fillers (calcium carbonate, CaCO3) and the polyvinylchloride resins (PVC) can be improved by adding oleochemical-based surfactant to the CaCO3, prior to its mixing with the plastic resins. A more homogeneous mixture was obtained, thus better PVC plastics was produced. This research was therefore undertaken to synthesize fatty alcohol-based phosphate ester using fatty alcohol as the starting material to be used as the coupling agent for the CaCO3 and plastics resins. In this study, the syntheses were carried out in three different routes and each route were divided into three steps. Fatty alcohol-based phosphate esters with diphosphate ester functional group were prepared by reacting a diol with phosphorus oxychloride (POCl3) and then followed by addition of long-chained fatty alcohol. In route one, C16-fatty alcohol was used in the synthesis. The optimized reaction temperatures for each step of reaction in this route were 20 °C, 35 ºC and 70 ºC respectively. The reaction duration of each step was about 3 hours. Excess of phosphorus oxychloride (2.5 mole) was used and 0.1% (w/w) of catalyst tetrabutyl orthotitanate (based on the weight of fatty alcohol) was employed in the synthesis. The percentage yield of the final product obtained from the titration of acidic solution (HCl gas in distilled water) with NaOH solution was about 60 %. From the GC, GC-MS, LC and LC-MS analyses, monophosphate ester (dipropyl heptadecyl phosphate ester) with the percentage of about 4.8% was obtained. While, the major compounds obtained were 1,6-dichlorohexane and 1-chlorohexadecane with the total percentage ~ 70%. In route two and three, the reactions were carried out under the reaction temperature of 20 °C, 90 ºC and 90 ºC for each step of the reaction respectively. The optimized reaction duration for each step was 2 hours, 2 hours and 1 hour respectively. In these syntheses, excess of phosphorus oxychloride (2.5 mole) was also used but no catalyst was applied in the reaction. The fatty alcohol used in route three was different with route one and two, whereby C18-fatty alcohol was used. The percentage yield of the final product obtained under these conditions was about 10-40% (by titration method). From the GC-MS and LC-MS analyses, the major compounds obtained from the synthesis were also 1,6-dichlorohexane and 1-chlorohexadecane which gave a total yield of ~74.06%. The phosphate ester obtained in this synthesis was a diphosphate ester (trihexadecyl hexyl diphosphate ester) with the percentage of about ~ 2.5%. Finally the products obtained were applied in PVC compounding. Some basic formulations were prepared, which comprised the synthesized phosphate ester (PE/T10), PVC resin, plasticizer (DOP), stabilizer (TBLS) and calcium carbonate as filler (CaCO3). The mixture of these polymers and additives was blended at 170 ºC with a mixing speed of 70 r.p.m. The homogenized plasticized mixture was then compressed on a hot press at 170 ºC for 10 min. Based on the tensile strength results, a slight decreased in the tensile properties was observed when the ester sample was added into the PVC compounding which could be due to the presence of chlorinated compound present as indicated by the analyses. The chlorinated compound may have reacted with the filler (CaCO3) during the PVC compounding process and thus causing the decreased in tensile strength of the plastic sheets. However, in general, the physical appearance of the PVC sheet could be improved by the synthesized phosphate ester (PE/T10) after further dried with anhydrous calcium sulphate whereby a smooth surface was observed compared to the PVC sheet without added of phosphate ester (PE/T10).